POTENTIAL MICROALGA Chlorella vulgaris FOR BIOREMEDIATION OF HEAVY METAL Pb - Halima, Asyatul; Nursyirwani, Nursyirwani; Effendi, Irwan; Ambarsari, Hanies (Asian Journal of Aquatic Sciences, 2019)
This research was conducted from April to July 2019 at the Center for Environmental Technology Laboratory (PTL), Geostech 820 Building, Serpong Region Puspitek, South Tangerang. The aim of this research was to determin growth of Chlorella vulgaris on media added with Pb at different concentrations, and to determine the ability to absorb Pb. The experimental method was conducted by using concentrations of Pb at 3 different levels consisting of 1 ppm, 5 ppm, 10 ppm in triplicate and control treatment without the addition of Pb. Each sample was analyzed by ICP-OES (Inductivly Coupled Plasma – Optical Emission Spectrometer). Data was analyzed by using ANOVA followed by LSD test. The growth of C. vulgaris biomass during the cultivation were Pb 1 ppm (10.38 g / l), k (9.10 g / l), Pb 5 ppm (8.36 g/l) and Pb 10 ppm (7.13) g/l). ANOVA test showed that different concentrations of Pb gave a very significant difference (Sig. <0.05) on the growth of C. vulgaris. Reduction in the concentration of Pb metal in culture media were Pb 10 ppm (96.8%), Pb 5 ppm (96.2%), Pb 1 ppm (90%) and there is no Pb found in control. ANOVA test results showed that C. vulgaris had a very significant effect (Sig. <0.05) on the decrease of Pb metal concentration. This shows that C. vulgaris has the capacity as bioremediation of Pb with different concentrations